Composite Strike-Slip Deformation Belts and Their Control on Oil and Gas Reservoirs: A Case Study of the Northern Part of the Shunbei 5 Strike-Slip Deformation Belt in Tarim Basin, Northwestern China - Yuan, Haowei; Chen, Shuping; Neng, Yuan; Zhao, Huaibo; Xu, Shidong; Wang, Xinpeng; Feng, Guimin (Frontiers in Earth Science, 2021)
Strike-slip deformation belts are interesting structures in the crust and are of significance in petroleum exploration. The Shunbei 5 fault belt (SB5), a long strike-slip deformation belt in the Tarim Basin, played an important role in the formation of a recently discovered major oilfield known as the Shunbei oilfield. In this study, models of plan view and vertical profile were established to interpret SB5 with multi-cycled tectonic activities. To this end, its structural framework, tectonic evolution, and associated plate tectonics were investigated using 2D and 3D seismic data. SB5 was formed as a dextral simple shear belt at the end of the Middle Ordovician. In the plan view, R-shears and P-shears with local transpressional and transtensional structures were observed. Along the vertical profiles, various structural styles occurred at various depths and strata in response to various stratigraphy mechanisms. Although these structures show clear boundaries between them, they correspond to the same formation time, indicating that they underwent deformation simultaneously. The second activity of SB5 occurred at the end of the late Ordovician, during which it was a dextral transtensional strike-slip deformation belt consisting of left-stepping en echelon R-shears. The R-shears were transtensional during the progressive deformation. Subsequently, SB5 underwent several strike slips of weak strength. Notably, SB5 cut through a deep Middle Cambrian gypsum salt layer and connected the deep Lower Cambrian source rock with deep Lower and Middle Ordovician carbonates to form the oil and gas reservoirs. The established models are of reference value in the interpretation of other subsurface strike-slip deformation belts.